2019
DOI: 10.1073/pnas.1814506116
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian insufficiency and CTNNB1 mutations drive malignant transformation of endometrial hyperplasia with altered PTEN/PI3K activities

Abstract: Endometrioid endometrial carcinomas (EECs) carry multiple driver mutations even when they are low grade. However, the biological significance of these concurrent mutations is unknown. We explored the interactions among three signature EEC mutations: loss-of-function (LOF) mutations inPTEN, gain-of-function (GOF) mutations of phosphoinositide 3-kinase (PI3K), andCTNNB1exon 3 mutations, utilizing in vivo mutagenesis of the mouse uterine epithelium. While epithelial cells with a monoallelic mutation in any one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 77 publications
2
19
0
Order By: Relevance
“…However, current models suggest that EIN/AH is a neoplastic process that arises in NAH, a physiologic process 35 . Activating mutations in EMC‐associated genes are often present in EIN/AH, 9,36‐38 in keeping with this model. Expanding these observations, we have shown that NAH harbors mutations, including the most common driver mutations in EMC, such as those involving PTEN , PIK3CA , and KRAS , and this suggests that it is neoplastic in the majority of cases.…”
Section: Discussionmentioning
confidence: 71%
“…However, current models suggest that EIN/AH is a neoplastic process that arises in NAH, a physiologic process 35 . Activating mutations in EMC‐associated genes are often present in EIN/AH, 9,36‐38 in keeping with this model. Expanding these observations, we have shown that NAH harbors mutations, including the most common driver mutations in EMC, such as those involving PTEN , PIK3CA , and KRAS , and this suggests that it is neoplastic in the majority of cases.…”
Section: Discussionmentioning
confidence: 71%
“…Recent work (30) showed that genetic changes in Pten, phosphatidylinositol-4,5bisphosphate 3-kinase catalytic subunit alpha (Pik3ca), and catenin beta 1 (Ctnnb1) within the mouse uterine epithelium were not sufficient for malignant transformation.…”
Section: No Effect On the Frequency Of Poorly-differentiated Adenocarmentioning
confidence: 99%
“…However, ovarian insufficiency was required for malignant transformation of those "triple" mutant endometrial epithelial cells (30). To determine the effects of ovarian insufficiency in dcKO mice, both ovaries were removed, and uterine weight and histology were assessed.…”
Section: No Effect On the Frequency Of Poorly-differentiated Adenocarmentioning
confidence: 99%
See 1 more Smart Citation
“…In a transgenic mouse model of OC, malignant transformation in endometriosis with mutation of Kras and p53 deletion within the ovarian surface epithelium showed hyperproliferative endometrioid glandular morphology [154]. Endometrial endometroid cancer (EEC) may be developed in a mouse model by the concurrent involvement of loss of function in PTEN, gain of function of PI3K and CTNNB1 [155].…”
Section: Oncogenes and Tumor Suppressor Genesmentioning
confidence: 99%